The Influence of Social-media on Agenda-setting in Nepali Journalism - Dahal, Rishikesh (Patan Prospective Journal, 2023)
This article examines the influence of social media on traditional media's role in shaping public opinion and agenda-setting in Nepal. Social media has emerged as a powerful medium, surpassing traditional media in terms of influence and reach. Drawing on the theoretical framework of agenda-setting, this study explores the current state of social media in Nepal. Using case studies and interviews with experts as primary sources and considering social media's purpose, use, and impact, the article presents a comprehensive analysis. The findings reveal that social media increasingly plays a stronger role in agenda-setting, while traditional media's ability to shape opinions and facilitate debates is diminishing. With its fast-paced dissemination, affordability, and visible impact, social media has overtaken traditional media in setting the agenda. However, the unrestricted production of content on social media poses risks, as it lacks an editing process. Traditional media, now relying on social media, faces intensified competition. To remain relevant and avoid weakening, news media must invest in content research and adapt to changing usage patterns. Upholding journalistic standards while leveraging the strengths of social media is crucial for traditional media in Nepal.